The Urgency of Value Education in Forming Students' Character in The Era of Society 5.0 - Fadilatul Alfusanah; Edo Ramada; Ayun Hafifatul Mukarohmah; Asep Fathurrohman; Chairul Anwar; Syaiful Anwar (The Future of Education Journal, 2024)
The Society 5.0 era is marked by technological advances that integrate the digital and physical worlds, presenting challenges in maintaining good moral values ​​and character amidst digital transformation. Value education is a crucial element in building a generation that is not only intellectually intelligent but also has ethical awareness, social responsibility, and high morality. This type of research includes library research. This study shows that education such as tolerance, respect, justice, honesty, empathy, and responsibility. Value education aims to improve social conditions and improve the nation's morals because the content of value education is intended to prevent juvenile delinquency, moral degradation and others. The results of this study are expected to provide guidance for educators in integrating character values ​​into the learning process so that students are able to face the challenges of the digital era with balanced competencies between technological and ethical aspects.